Analysis of Determinants of Interest in Continuing Higher Education among Female Students at SMKN 2 Pangkep Regency, South Sulawesi - A. Nur Maida; Hamidah Suryani; Muhlis (PT ARRUS Intelektual Indonesia, 2026)
Vocational high school education plays an important role in equipping female students with vocational skills. This study is a quantitative study with an inferential approach that aims to analyze the determinants that influence the interest in continuing higher education among female students at SMKN 2 Pangkep Regency, South Sulawesi, by taking a random sample with a population of 100 female students majoring in Fashion Design and a sample of 42 female vocational school students. Data collection methods included observation, interviews, and questionnaires. Data analysis used multiple linear regression statistics to test the significance of the influence of each variable. The results of the study show that the interest of SMKN 2 Pangkep Regency students in continuing higher education is simultaneously influenced by intrinsic and extrinsic factors. Intrinsic factors contributed 71.8%, which included learning motivation, self-efficacy, academic interest, desire to achieve, and future orientation, indicating a fairly strong internal drive but not yet fully stable because it was still influenced by individual psychological conditions. Meanwhile, extrinsic factors have a more dominant influence with a contribution of 74.2%, which includes family support (78%), the role of teachers (75%), the school environment (73%), the influence of peers (72%), and access to educational information (73%). These findings indicate that students' interest in pursuing higher education is not only determined by personal awareness but is also greatly influenced by social and educational support. Thus, increasing interest in higher education among vocational high school students requires a collaborative strategy through strengthening internal motivation and external support from families, schools, and adequate access to educational information.